Clinical Outcome in Gamma Knife Radiosurgery for Metastatic Brain Tumors from the Primary Breast Cancer : Prognostic Factors in Local Treatment Failure and Survival - Choi, Seung Won (The Korean Neurosurgical Society, 2013)
OBJECTIVE: Brain metastases in primary breast cancer patients are considerable sources of morbidity and mortality. Gamma knife radiosurgery (GKRS) has gained popularity as an up-front therapy in treating such metastases over traditional radiation therapy due to better neurocognitive function preservation. The aim of this study was to clarify the prognostic factors for local tumor control and survival in radiosurgery for brain metastases from primary breast cancer. METHODS: From March 2001 to May 2011, 124 women with metastatic brain lesions originating from a primary breast cancer underwent GKRS at a tertiary medical center in Seoul, Korea. All patients had radiosurgery as a primary treatment or salvage therapy. We retrospectively reviewed their clinical outcomes and radiological responses. The end point of this study was the date of patient's death or the last follow-up examination. RESULTS: In total, 106 patients (268 lesions) were available for follow-up imaging. The median follow-up time was 7.5 months. The mean treated tumor volume at the time of GKRS was 6273 mm(3) (range, 4.5-27745 mm(3)) and the median dose delivered to the tumor margin was 22 Gy (range, 20-25 Gy). Local recurrence was assessed in 86 patients (216 lesions) and found to have occurred in 36 patients (83 lesions, 38.6%) with a median time of 6 months (range, 4-16 months). A treated tumor volume >5000 mm(3) was significantly correlated with poor local tumor control through a multivariate analysis (hazard risk=7.091, p=0.01). Overall survival was 79.9%, 48.3%, and 15.3% at 6, 12, and 24 months, respectively. The median overall survival was 11 months after GKRS (range, 6 days-113 months). Multivariate analysis showed that the pre-GKRS Karnofsky performance status, leptomeningeal seeding prior to initial GKRS, and multiple metastatic lesions were significant prognostic factors for reduced overall survival (hazard risk=1.94, p=0.001, hazard risk=7.13, p<0.001, and hazard risk=1.46, p=0.046, respectively). CONCLUSION: GKRS has shown to be an effective and safe treatment modality for treating brain metastases of primary breast cancer. Most metastatic brain lesions initially respond to GKRS, though, many patients have further CNS progression in subsequent periods. Patients with poor Karnofsky performance status and multiple metastatic lesions are at risk of CNS progression and poor survival, and a more frequent and strict surveillance protocol is suggested in such high-risk groups.